Influence of Different Types of Water Absorbent Polymers on Soil Properties, Plant Growth, and Irrigation Interval - Dahri, Shahzad Hussain; Mangrio, Munir Ahmed; Shaikh, Irfan Ahmed; Dahri, Zakir Hussain; Ali, Irfan; Mangrio, Abdul Ghafoor; Saleem, Salman; Aqlani, Zaheer Ahmed; Brohi, Sheeraz Aleem; Dahri, Zamin Hussain (AGRIVITA Journal of Agricultural Science, 2026)
Water and minerals are the key resources for citrus production. However, their excessive use can hinder plant growth and lead to economic losses. This study aimed to evaluate the effects of different polymers on soil properties, lemon plant growth, irrigation intervals, and water saving. The treatments were control (T0), water-pad polymer laid at the bottom of the plant pit (T1), polymer in powder form at 3 g/kg of soil (T2), and polymer in crystal form at 3 g/kg of soil (T3). To avoid seepage losses, a plastic polyethylene sheet was placed along each side of the pit, and one-year-old lemon plants were transplanted in each pit. The results show that soil physical and chemical properties significantly improved in all treatments when compared with the control treatment. The improved hydro-physical characteristics increased the irrigation interval and reduced the number of irrigations by 50%. The accumulation of soil minerals (Ca and Mg) and soil cations (K and Na) was significantly increased than control. Water saving of 39% and substantial improvement in plant growth were observed in all polymer treatments. The water and mineral saving and significant improvement in plant growth show the hydrogel as a resilient soil amendment for plant growth and economic benefits.